Penilaian Kenyamanan Termal pada Ruang Baca Perpustakaan Umum Kota Pekalongan - Astrihasna Shafa; Suzanna Ratih Sari (RUAS, 2022)
Evaluation of thermal comfort in the 1st and 2nd-floor reading rooms of Pekalongan City Public Library is to support the aim of designing a comfortable reading room that can increase people's reading interest. This study uses a quantitative approach defined descriptively and evaluatively. Direct measurement data in the morning and afternoon using a thermometer, hygrometer, and anemometer for four days. Data also uses a questionnaire. The collected data compares the measurement analysis results with recommended standards. The result shows that the reading room on the 1st floor was in the threshold and heat-comfort category, which was around 26℃ - 27.4 ℃, while the reading room on the 2nd floor was in the optimal comfortable category, which was around 24.7℃ - 26.4℃. The effective temperature of the 1st-floor reading room is higher than the 2nd floor. The final result shows that the room is in the less comfortable category because the air conditioner in the reading room is not as it should be appropriate.